Financially Linked Independent Directors and Bankruptcy Reemergence: The Role of Director Effort. (September 2018) - Arora, Punit
This study examines if the effort of financially linked independent (FLI) directors enable firms to reemerge from bankruptcy, a major organizational crisis. Using a sample of 307 bankrupt U.S. firms with instrumental variables regression methodology, I find that the efforts of these directors are critical for firm reemergence. FLI directors' efforts increase the likelihood of reemergence as well as improve access to financial resources. In contrast, I do not find any evidence that non-FLI directors' efforts are associated with reemergence. I also find that resourceful but uninvolved directors are not helpful for firms trying to navigate their way out of bankruptcy. My study highlights (a) the changing nature of roles played by directors in various lifecycle stages, (b) the greater importance of resource provisioning over monitoring during reemergence, and (c) that efforts of FLI directors, and not others director categories, matter for reemergence. Overall, my study extends research that suggests directors' motivation may cause differential firm outcomes and provides evidence that directors do not always put in their best effort on behalf of their firms. This, I suggest, has profound implications for corporate governance research and practice.